Технологія косметичного крему-пілінгу з мінеральними абразивами - Полонська, Тетяна Анатоліївна (My University, 2018)
Дисертаційну роботу присвячено вирішенню конкретного науково-практичного завдання – розробки наукових засад технології емульсійних косметичних засобів з використанням нового мінерального ексфоліанту, ефективного в терапії хвороб шкіри. Досліджено ряд глинистих мінералів (сапоніт, бентоніт, клиноптилоліт, палегорскіт, глауконіт) з точки зору їх засосування як ексфоліантів мінерального походження. Обгрунтовано склад жирової фази емульсії з кокосової, кунжутної, пшеничної олій у співвідношенні 1:1:1 з адекватним для нормальної здорової шкіри співвідношенням жирних кислот. Дослідженням каскаду розтікання підтверджено склад композиції трьох олій, що забезпечують оптимальне всмоктування і розтікання суміші під час нанесення на шкіру. Запропоновано застосування глауконіт-крохмальної композиції з 0,5 %мас високодисперсного порошку глауконіту в якості водної фази емульсій для агрегативної та седиментаційної стійкості структурованої системи. Розроблено удосконалену технологію та рецептуру косметичного крему-пілінгу мінерального, що за органолептичними, фізико-хімічними і мікробіологічними показниками відповідає ДСТУ 4764:2007 і характеризується високими споживчими властивостями. Вивчено динаміку зміни рН та морфологічну картину зміни епідермісу групи волонтерів і доведено наявність лікувально-профілактичного ефекту після застосування розробленого крему-пілінгу. The thesis is dedicated to the solution of a specific scientific and practical task of developing scientific bases for the technology of emulsion cosmetic products with the use of the new mineral exfoliant effective in the treatment of skin diseases. A number of clay minerals (saponite, laponite, clinoptilolite, palegorskite, glauconite) have been studied from the point of view of their use as exfoliants of mineral origin. The glauconite is classified as a class of microporous samples with a small outer surface and a radial-spherical structure of high purity. The surface properties of the glauconite mineral are explained because of the existence of a "carpet" of oxygen atoms on the surface of the mineral due to the formation of hydrogen bonds with adsorbed molecules. It has been proved that it is possible in principle to design natural oil compositions with a favorable composition of fatty acids, which corresponds to the composition of the lipid layers of the barrier layer of the skin. The composition of the fatty phase of the emulsion from coconut, sesame, wheat oil in a ratio of 1:1:1 with an adequate ratio of fatty acids to normal healthy skin is substantiated. Investigation of the cascade of spreading confirmed the composition of the composition of three oils, ensuring optimal absorption and spreading of the mixture when applied to the skin. It has been suggested to use 0.5% by weight highly dispersed glauconite powder in the complex emulsifier from a mixture of mono- and diesters of oleic acid and mono- and diesters of stearic acid in a ratio of 2:1. It has been proved that glauconite concentrates on the interphase boundary with the formation of a strong spatial coagulation structure and allows not only to ensure 100% stability of the emulsion, but also its long lifetime without additional application of stabilizers.
Keywords: технологія косметичних засобів; емульсія; глауконіт; функціональна ефективність; technology of cosmetic products; emulsion; glauconite; functional efficiency; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів